Optimal placement and sizing of electric vehicle charging stations on distribution systems for enhanced power system stability - Lau, Tiong Kiang (2024)
The integration of Electric Vehicle (EV) charging stations with power distribution networks is crucial for advancing sustainable transportation. This study addresses the vital need for optimal placement and sizing of EV charging stations to enhance power system stability. Failure to conduct these studies could lead to suboptimal network performance, increased power losses, and reduced reliability. As the demand for reliable and accessible EV charging infrastructure grows, challenges in grid integration become apparent, necessitating a thorough investigation into the optimal placement and sizing of these stations.